FORMULASI SEDIAAN HAIR TONIC EKSTRAK ETANOL DAUN TEH HIJAU (Camellia sinensis L.) SEBAGAI PENUMBUH RAMBUT TERHADAP KELINCI JANTAN (Oryctolagus cuniculus) - Sembiring, Pintata (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Background: hair loss is less or more hair than normal, with or without visible thinning. Green tea leaf minoxidil, whixh contains flavonoid compounds that may prevent hair loss, can be used to treat hair loss. Objective: this study aims to confirm whether green tea leaf ethanol extract can be used as a hair restorer that meets the requidments of physical stability, and to investigate the efficacy of green tea leaf extract hair restorer compared with minoxidil on hair growth purpose. Methods: This study used an experimental method that was macerated using 96% ethanol as a solvent. The formula was made into 3 concentrations, namely 2.5%; 5%; 7.5% compared with the drug minoxidil as a positive control. The three formulas were first evaluated to meet the requirements for hair tonic stability, then the hair effectiveness test was carried out with the test animal being a male rabbit. Results: the group that had the highest effectiveness on hair growth in rabbits was minoxidil which had an average value on the 7th, 14th and 21st days of 4.9 ; 6.3 ; 7.9 followed by the third formula which has a concentration of 7.5% as much as 4.5; 5.2 ; 6.5. While the negative control which was only applied with a hair tonic base only had hair growth 1,4; 1,9 ; 2,3. Conclusion: The preparation of hair tonic formula 1 to formula 3 met the requirements for physical stability, namely, pH test, viscosity test and organoleptic test. The preparation of hair tonic ethanol extract of green tea leaves (Camellia sinensis L.) showed that the 7.5% concentration was more effective in accelerating hair growth compared to formulas 1 and 2, and also showed that the 7.5% concentration had almost the same effectiveness as minoxidil (positive control).